2015
DOI: 10.1016/j.cub.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of a Putative Reinforcement Signal Conditions Cued Interval Timing in Primary Visual Cortex

Abstract: Summary As a consequence of conditioning visual cues with delayed reward, cue-evoked neural activity that predicts the time of expected future reward emerges in the primary visual cortex (V1). We hypothesized that this reward timing activity is engendered by a reinforcement signal conveying reward acquisition to V1. In lieu of behavioral conditioning, we assessed in vivo whether selective activation of either basal forebrain (BF) or cholinergic innervation is sufficient to condition cued interval timing activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 51 publications
12
66
0
Order By: Relevance
“…Computational studies have shown that cue-reward intervals can be expressed in V1 single units through reward-dependent expression of synaptic plasticity (Gavornik et al, 2009;Gavornik and Shouval, 2011). According to this reward-dependent expression model, V1 receives a local reinforcement signal, as recently experimentally observed (Liu et al, 2015), that selectively enables changes in synaptic weights of those synapses that have been active in the recent past. The population reward timing signal evidenced in V1's LFP arises with training as a result of oscillations becoming longer or shorter to match the animal's behavioral reward time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Computational studies have shown that cue-reward intervals can be expressed in V1 single units through reward-dependent expression of synaptic plasticity (Gavornik et al, 2009;Gavornik and Shouval, 2011). According to this reward-dependent expression model, V1 receives a local reinforcement signal, as recently experimentally observed (Liu et al, 2015), that selectively enables changes in synaptic weights of those synapses that have been active in the recent past. The population reward timing signal evidenced in V1's LFP arises with training as a result of oscillations becoming longer or shorter to match the animal's behavioral reward time.…”
Section: Discussionmentioning
confidence: 98%
“…Cortical representations of visual inputs in the adult animal can be modified by a variety of manipulations, such as repeated exposure (Fiorentini and Berardi, 1980;Furmanski et al, 2004;Frenkel et al, 2006;Gavornik andBear, 2014), visual deprivation (Sawtell et al, 2003;Hofer et al, 2006), attentional demands (Ahissar and Hochstein, 1993;Fahle, 2004), and positive reinforcements (Serences, 2008;Seitz et al, 2009;Stȃnişor et al, 2013). These changes in V1 responses are generally interpreted in a perceptual learning framework, wherein visual experience improves our ability to perceive the world (Karmarkar and Dan, 2006;Gilbert et al, 2009;Roelfsema et al, 2010). Here we demonstrate that, with training, stimulus-evoked oscillations in V1 lose their relationship with the physical parameters of the stimuli and evolve to relate to the behavioral meaning, as acquired through training, that the stimuli foretell: reward time and prior reward history but not reward magnitude itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But which part of your brain is actually involved in generating this expectation? In a series of recent papers [1][2][3], one published in this issue of Current Biology [4], Shuler and colleagues present a surprising answer: it is, at least in part, your primary visual cortex.…”
mentioning
confidence: 99%
“…These reward-timing responses come in three different varieties: some neurons show sustained activation from stimulus presentation to the expected time of reward, others show inhibition during the same period, and a third group exhibits a firing rate peak at the expected reward time ( Figure 1B). Liu et al [4] in this issue build on this work to better understand the mechanisms by which V1 neurons can be trained to exhibit such responses.…”
mentioning
confidence: 99%